Numerical and experimental investigation of direct solar crop dryer for farmers - Kareem, M.W. (American Institute of Physics Inc., 2015)
This article presents a theoretical and experimental investigation on effects of weather on direct solar crop drying technique. The SIMULINK tool was employed to analyze the energy balance equations of the transient system model. A prototype of the drying system was made and data were collected between the months of June and July in Perak, Malaysia. The contribution of intense sunny days was encouraging despite the wet season, and the wind velocity was dynamic during the period of investigation. However, high percentage of relative humidity was observed. This constitutes a hindrance to efficient drying process. The reported studies were silent on the effect of thick atmospheric moisture content on drying rate of agricultural products in tropic climate. This finding has revealed the mean values of insolation, wind speed, moisturized air, system performance efficiency and chili microscopy image morphology. The predicted and measured results were compared with good agreement. Â© 2015 AIP Publishing LLC.